Lit up and left dark: Failures of imagination in urban broadband networks. (December 2018) - Halegoua, Germaine R; Lingel, Jessa
The design and deployment of urban broadband infrastructures inscribe particular imaginations of Internet access onto city streets. The different manifestations and locations of these networks, their uses, and access points often expose material excesses of urban broadband networks, as well as failures of Internet service providers, urban planners, and public officials to imagine the diverse ways that people incorporate Internet connection into their everyday lives. We approach the study of urban broadband networks through the juxtaposition of invisible networks that are buried under the streets and have always been "turned off" (dark fiber) versus hypervisible that are "turned on" and prominently displayed on city streets (LinkNYC). In our analysis of these two case studies, we critique themes of visibility and invisibility as indexes of power and access. Our findings are meant to provide a critical analysis of urban technology policy as well as theories of infrastructure, visibility, and access.